Field Synergy Analysis and Optimization of the Thermal Behavior of Lithium Ion Battery Packs - He, Hongwen; Jia, Hui; Huo, Weiwei; Sun, Fengchun (Energies (Basel), 2017)
In this study, a three dimensional (3D) modeling has been built for a lithium ion battery pack using the field synergy principle to obtain a better thermal distribution. In the model, the thermal behavior of the battery pack was studied by reducing the maximum temperature, improving the temperature uniformity and considering the difference between the maximum and maximum temperature of the battery pack. The method is further verified by simulation results based on different environmental temperatures and discharge rates. The thermal behavior model demonstrates that the design and cooling policy of the battery pack is crucial for optimizing the air-outlet patterns of electric vehicle power cabins.